Facades-as-a-Service - Juan F. Azcárate-Aguerre (A+BE: Architecture and the Built Environment)
Facades-as-a-Service (FaaS) is a systemic innovation model aiming to accelerate and enhance the energy and comfort performance improvement of our buildings, while safeguarding the availability of material resources for future generations. The circular economy and clean energy transitions in the built environment have respectively dominated the academic dialogue in architecture, engineering, and real estate over the last decades. While significant progress has been made, and many fine examples of more sustainable architecture exist, the process has been hindered by traditional systemic models for the planning, contracting, financing, construction, and management of building projects. If we are to meet the ambitious climate-change mitigation goals and material resource preservation challenges of our generation, it is crucial to re-think the way in which we build, operate, and decommission the built environment. Product-service systems (PSS) are a promising model for realigning environmental risks and responsibilities with financial and business objectives, while promoting much deeper and long-lasting collaboration between all parties involved in a building’s life-cycle. This thesis focuses on the building envelope, as one of the most performance-determining systems in our buildings. It then questions the technological, managerial, financial, and legal contexts which often perpetuate unsustainable linear practices despite the urgency for - and technical feasibility of - more energy- and resource-efficient alternatives. Facades-as-a-Service is a topic that extends far beyond technological readiness and architectural engineering. It is rather a thesis about how we make façade construction and retrofitting decisions, the systemic parameters that determine and constraint these decisions, and whether – in the search for a more sustainable built environment – we should question the fundamental concepts behind these decisions. The results show that gradual and strategic development with a multi-disciplinary perspective can enable and facilitate the implementation of more efficient and sustainable building practices.